Learner Agency and Assessment for Learning in a Regional New Zealand High School - Charteris, Jennifer (Australian and International Journal of Rural Education, 2015)
Assessment for Learning (AfL) pedagogies can have a significant impact on student learning and achievement. This paper reports on data from a study of four teachers and 48 student participants within a regional high school. An inquiry approach to teacher professional learning is explored through an AfL lens, in particular, how teacher feedback for professional learning can be nuanced and dialogic. The research draws from one reflective dialogue interview where a teacher explores student voice data to consider her learners’ perceptions of how they learn and of the classroom learning practices of feedback, feedforward and self-assessment. The paper addresses learner agency as an important aspect of curriculum implementation for teachers and assessment for learning for students.